Representative Bureaucracy Theory and the Implicit Embrace of Whiteness and Masculinity. (21st February 2022) - Portillo, Shannon; Humphrey, Nicole; Bearfield, Domonic A.
Abstract: Throughout much of representative bureaucracy literature, scholars have primarily focused on the representation of people seen as other in the professional workforce—people of color and women. However, whiteness and masculinity have been central to the development of public administration as a field of scholarship and practice. As a field, we have often avoided explicit discussions regarding the impact whiteness and masculinity. We argue that silences around race and gender have significant implications. Using representative bureaucracy as a frame, we seek to highlight how acknowledging whiteness and masculinity in our scholarship can help provide a more comprehensive understanding of race and gender in public administration.